PHYTOCHEMICAL SCREENING OF AQUEOUS AND METHANOL EXTRACTS OF LEAF AND ROOT BARK OF Gardenia ternifolia (SCHUMACK AND THONNS) - Onyilokwu, Comfort Anyalewa; Onwumere, Godwin Brian; Dan, Victoria Moltong Yilwa (FUDMA JOURNAL OF SCIENCES, 2026)
Gardenia ternifolia is a shrub of the Rubiaceae family that is harvested in the wild for protection against evil spirit as it is believed that the plant has protective charm property. The study aim to determine the phytochemicals constituents and mineral compositions of aqueous and methanol extracts of the leaf and root bark of G. ternifolia. The leaves and root of Gardenia ternifolia were obtained from the wild in Akpegede in Otukpo Local Government Area of Benue State. The sample was rinsed and air dried in a shade, then pulverized. Extracts from the plant parts were gotten using water and methanol solvent. Thereafter, qualitative phytochemicals and minerals constituents was screened. The phytochemicals present in both aqueous and methanol extracts include carbohydrates, phenols, flavonoids, alkaloids, tannins, steroids, saponins, triterpenes and cardiac glycosides in different proportions. While, the minerals found include iron, copper, zinc, nickel, lead and cobalt.